2017
DOI: 10.18001/trs.3.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Using the Vape Shop Standardized Tobacco Assessment for Retail Settings (V-STARS) to Assess Product Availability, Price Promotions, and Messaging in New Hampshire Vape Shop Retailers

Abstract: Objectives This is the first statewide census of the product availability, price promotions, and product messaging of vape shops. Methods A comprehensive list of New Hampshire vape shops was developed through a previously validated online search method. Store audits were conducted in 55 stores between January and February 2016 using the Vape Shop Standardized Tobacco Assessment for Retail Settings (V-STARS). Results Modifiable devices and cig-alikes were sold in 92.6% and 14.6% of stores, respectively. Cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 20 publications
2
30
0
Order By: Relevance
“…Within the literature regarding vape shops, prior research indicates a large proportion (~45%) of vape shops carry CBD and/or THC products. ( Kong et al, 2017 , Berg et al, 2020 ) However, to our knowledge, no prior research has asked vape shop merchants about their perceptions of CBD or marijuana products, their interest in those markets, or their perceptions about legalized marijuana retail. Findings from the current study indicated few areas of consensus across topics explored.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the literature regarding vape shops, prior research indicates a large proportion (~45%) of vape shops carry CBD and/or THC products. ( Kong et al, 2017 , Berg et al, 2020 ) However, to our knowledge, no prior research has asked vape shop merchants about their perceptions of CBD or marijuana products, their interest in those markets, or their perceptions about legalized marijuana retail. Findings from the current study indicated few areas of consensus across topics explored.…”
Section: Discussionmentioning
confidence: 99%
“…( Lee et al, 2018 ) Intuitively, the increasing prevalence of vaping marijuana, particularly in states with legalized marijuana, ( Goodman et al, 2020 ) suggests that vape shops may profit from catering to CBD and/or marijuana consumer markets. ( Tully, 2020 ) One study examined the New Hampshire vape shops and head shops ( Kong et al, 2017 ) (e.g., outlets specializing in smoking products and accessories [e.g., hookah tobacco/pipes, blunt wraps, bongs], including vaping products Giovenco, 2018 ). Despite neither CBD- nor THC-containing products being legal in New Hampshire, 6% of vape shops and 47% of vape/head shops sold CBD- and/or THC-containing products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To fill an important gap in research on marijuana retail marketing, this study builds on the development and pilot testing of the Marijuana Retail Surveillance Tool (MRST), conducted in a convenience sample of 20 Denver retailers ( Berg et al, 2017 ). The MRST was based on relevant and reliable measures, specifically a premise survey used to characterize medical marijuana dispensaries in California ( Thomas & Freisthler, 2016 ) and the vape shop module of the Standardized Tobacco Assessment for Retail Settings (V-STARS) ( Kong et al, 2017 ). Reviews of the literature were conducted to inform assessments of product offerings (e.g., ( Bierut et al, 2017 )), as well as promotional strategies used on marijuana retailer websites (e.g., ( Bierut et al, 2017 )).…”
Section: Introductionmentioning
confidence: 99%
“…However, a higher percentage of older adult smokers who vape use disposables (51%) than later generation models (41%) 19 . Certainly, store owners perceive e-cigarettes as much more safe than combustible cigarettes 12 , offer sophisticated marketing approaches, including loyalty point incentives for customers, and make vape shops an environment in which customers can socialize 1,12,20,21 .…”
Section: Introductionmentioning
confidence: 99%